Effect of Drinking - Beverages (Alcohol, Caffeine and Soda) Against Stomach Disease UINFAS Bengkulu Students: Effect of Drinking - Beverages (Alcohol, Caffeine and Soda) Against Stomach Disease UINFAS Bengkulu Students - Zakhi Restu Paratama; Dian Ayu Rahmadhani; Dendo Pratama; Dendo Paratama; Meirita Sari; Kingkin Dia Pita Loka (LPPM IAI As-Siddiq Kie Raha Maluku Utara, 2023)
Abstrac Ulcer disease is a problem often experienced by students because of several factors that influence it. This research aims to determine the effect of drinking (alcohol, caffeine and soda) on ulcer disease among UINFAS Bengkulu students. The method used is a quantitative method where we use prerequisite tests, namely the normality test, linearity test and simple linear regression test with data collection techniques through questionnaire questions using Google Form which are distributed to students at UIN Fatmawati Sukarno Bengkulu which consists of 4 faculties, namely: FTT, FEBI, FUAD and Sharia. The sample used was 40 students. The questions used consisted of 20 questions consisting of 3 categories, namely: (Student knowledge, causal factors and healthy lifestyles against stomach ulcers). The results obtained from the data show that students are of the same size. In conclusion, the influence of drinking (alcohol, caffeine and soda) has a significant influence of 47% on the ulcer disease of UINFAS Bengkulu students. In order to reduce the risk of developing stomach ulcers in students, it is important to increase awareness of the negative impacts of consuming alcohol, caffeine and soda. Students need to be informed about healthier drink alternatives and encourage a balanced lifestyle. In addition, further research needs to be carried out to explore the relationship between consumption of these drinks and stomach ulcers and explore other factors that may influence the risk of stomach ulcers in the student population. Keyword : Student Lifestyle, Beverage Consumption, Gastric Disorders, and Gastrointestinal Diseases